COUNSELING SERVICES BASED RESEARCH TO IMPROVE THE QUALITY OF LEARNING THROUGH COUNSELING - Ardimen, Ardimen (Universitas Muhammadiyah Metro, 2016)
The purpose of writing this article is to describe the subject of study and reason as well as research-based counseling service management. Counseling services based on research carried out to improve the quality of learning through counseling. The discussion of this article are (1) the background of the counseling service based research, (2) understanding the tasks and activities of counseling teacher or counselor, (3) reason for the existence of counseling in education, (4) the differences and similarities counseling services with research PTK-BK, (5) the motivations and goals of research-based counseling services, and (6) management of research-based counseling services. Among the benefits of this article is to (1) raise awareness counseling teacher or counselor about the importance of developing a counseling service that is integrated with the research, (2) develop a research culture for counseling teacher/ counselor, (3) encourage educational institutions both school/ madrasah/ pesantren for developing research-based counseling services, (4) encourage universities that provide education academic and professional counseling to develop research activities and community service through mentoring research-based counseling services. Keywords: counseling services, research, quality of learning, PTK-BK.